A comprehensive analysis of racial disparities in chemical biomarker concentrations in United States women, 1999–2014. (April 2020) - Nguyen, Vy Kim; Kahana, Adam; Heidt, Julien; Polemi, Katelyn; Kvasnicka, Jacob; Jolliet, Olivier; Colacino, Justin A.
Highlights: Characterized racial disparities for 143 chemical biomarkers across 38, 080 US women. Metals, pesticides, and chemicals in consumer products show the highest disparities. Some disparities, like 2, 4- and 2, 5-dichlorophenol, persist across age groups. Methyl and propyl paraben disparities are greatest in children. Disparities for arsenics, parabens, phenols, and cotinine persist over time. Abstract: Background: Stark racial disparities in disease incidence among American women remain a persistent public health challenge. These disparities likely result from complex interactions between genetic, social, lifestyle, and environmental risk factors. The influence of environmental risk factors, such as chemical exposure, however, may be substantial and is poorly understood. Objectives: We quantitatively evaluated chemical-exposure disparities by race/ethnicity, life stage, and time in United States (US) women (n = 38, 080) by using biomarker data for 143 chemicals from the National Health and Nutrition Examination Survey (NHANES) 1999–2014. Methods: We applied a series of survey-weighted, generalized linear models using data from the entire NHANES women population along with cycle and age-group stratified subpopulations. The outcome was chemical biomarker concentration, and the main predictor was race/ethnicity with adjustment for age, socioeconomic status, smoking habits, and NHANES cycle. Results: Compared to non-Hispanic White women, the highest disparities were observed for non-Hispanic Black, Mexican American, Other Hispanic, and Other Race/Multi-Racial women with higher levels of pesticides and their metabolites, including 2, 5-dichlorophenol, o, p'-DDE, beta-hexachlorocyclohexane, and 2, 4-dichlorophenol, along with personal care and consumer product compounds, including parabens and monoethyl phthalate, as well as several metals, such as mercury and arsenic. Moreover, for Mexican American, Other Hispanic, and non-Hispanic black women, there were several exposure disparities that persisted across age groups, such as higher 2, 4- and 2, 5-dichlorophenol concentrations. Exposure levels for methyl and propyl parabens, however, were the highest in non-Hispanic black compared to non-Hispanic white children with average differences exceeding 4-fold. Exposure disparities for methyl and propyl parabens are increasing over time in Other Race/Multi-Racial women while fluctuating for non-Hispanic Black, Mexican American, and Other Hispanic. Cotinine levels are among the highest in Non-Hispanic White women compared to Mexican American and Other Hispanic women with disparities plateauing and increasing, respectively. Discussion: We systematically evaluated differences in chemical exposures across women of various race/ethnic groups and across age groups and time. Our findings could help inform chemical prioritization in designing epidemiological and toxicological studies. In addition, they could help guide public health interventions to reduce environmental and health disparities across populations.